Impacto de protocolos de telenutrição em um programa de aconselhamento nutricional on-line nas práticas alimentares de adultos - Santana, Francismayne Batista (2023)
Introduction: Telehealth has risen amid the Covid-19 pandemic. Telenutrition stands out, a modality that allows to promote the improvement of nutrition at a distance. The aim of this study was to evaluate the effectiveness of two different telenutrition protocols on the dietary practices of adults. Methods: A 12-week randomized controlled clinical trial of different telenutrition protocols with online nutritional counseling. Two protocols were conducted, the multicomponent (MT), composed of multiple strategies combined, synchronously and asynchronously, and the traditional (TD), with only synchronous strategy, in addition to the control group (CT), which received the written material. The primary outcome was assessed by the eating practices score. In addition, the realization of Food and Nutrition Education (FNE) actions in telehealth for the MT group stands out. Results: 86 individuals participated, 35 in the MT group, 30 in the TD and 21 in the CT. After 12 weeks, the MT and TD groups showed a significant increase in the dietary practices score (p=0.049), and both were different from the control (MT x CT: p< 0.001; η2: 0.21); (TD x CT: p=0.002; η2: 0.21). The MT showed significant changes in four evaluation items: fruit and nuts consumption, eating habits and intake of sweets and soft drinks (p=0.004; p=0.049; p=0.006 and p=0.025). On the other hand, DM showed significant results in two items: fruit consumption at breakfast and the habit of "pinching", also compared to TC (p=0.028; p=0.042). Regarding the EAN actions, it is noteworthy that they enabled greater knowledge of individuals about eating habits, with sharing experiences about food choices and the way of eating. In addition, it favored the strengthening of bonds and the continuity of dietary change. Conclusion: The multicomponent and traditional methodology were effective in improving eating practices, with emphasis on the combined methods in telenutrition. In addition, it is noteworthy that EAN actions represented an effective proposal aimed at promoting healthy eating habits within the scope of telehealth.